A method for preparing foam ceramic reinforced cement-based composite material

By using foam ceramics as the skeleton support structure and combining magnesium phosphate fast hard cement, ceramic-reinforced cement matrix composite materials are prepared, which solves the problem of insufficient mechanical properties and designability of cement materials under high temperature conditions, and achieves efficient molding and rapid assembly of materials.

CN117623696BActive Publication Date: 2025-04-15HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311838211.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2025-04-15
Estimated Expiration
2043-12-28

AI Technical Summary

Technical Problem

The mechanical properties and designability of existing cement materials under high temperature conditions are insufficient, and it is difficult to construct cement materials with ceramics on-site.

Method used

Foam ceramics are used as the skeleton support structure, combined with magnesium phosphate fast hard cement, and ceramic reinforced cement matrix composites are prepared through stirring, pouring and maintenance steps.

Benefits of technology

It improves the mechanical properties and designability of cement-based materials under high temperature conditions, simplifies the on-site construction process, and realizes rapid assembly and efficient molding of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117623696B_ABST
    Figure CN117623696B_ABST
Patent Text Reader

Abstract

A method for preparing a foam ceramic reinforced cement-based composite material relates to a method for preparing a ceramic reinforced cement-based composite material. The present invention aims to solve the technical problems of insufficient high-temperature mechanical properties and designability of current cement materials, as well as great construction difficulty. The present invention uses foam ceramics and magnesium phosphate rapid-hardening cement to quickly prepare a ceramic reinforced cement-based composite material, so that the cement-based material is strengthened while being rapidly hydrated, thereby expanding the application of cement materials in high-temperature fields, avoiding the problem of the difficulty in forming cement materials obtained by adding admixtures such as ceramsite, and improving the designability and simplicity of on-site construction of cement-based composite materials. Foam ceramics play a role in strengthening the cement matrix. On the one hand, the foam ceramic structure realizes the skeleton support of the cement material, and on the other hand, it improves the interface bonding between the ceramic reinforcement and the cement matrix. Composite materials of different densities can be obtained by adjusting the ratio of cement and foam ceramics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a ceramic reinforced cement-based composite material. Background Art

[0002] Magnesium phosphate cement is a special cement material with fast setting and hardening, strong volume stability, rapid early strength development, and good corrosion resistance. It has unique advantages in engineering applications such as highways and bridges. However, magnesium phosphate cement is similar to ordinary Portland cement in that it is a brittle material with poor deformation resistance. At the same time, like most cement materials, magnesium phosphate cement has poor high temperature resistance and is difficult to use in scenarios with high requirements for fire resistance and safety performance.

[0003] Alumina (Al2O3) ceramics and silicon carbide (SiC) ceramics have excellent mechanical properties and high temperature resistance. For example, SiC ceramics have excellent chemical corrosion resistance and wear resistance, and have excellent high temperature strength, good heat shock resistance, excellent thermal conductivity, and low thermal expansion coefficient. Foam ceramics are the third generation of porous ceramic products that have been developed recently. They have excellent high temperature mechanical properties and good molding and processing properties. By changing the processing conditions, foam ceramics of different shapes, sizes, porosities, and pore sizes can be obtained. If magnesium phosphate cement can be combined with ceramic materials with excellent performance, using the advantages of magnesium phosphate cement's rapid hardening and early strength, and the excellent high temperature mechanical properties of ceramic materials, a new type of ceramic reinforced cement-based material will be obtained. Summary of the invention

[0004] The present invention aims to solve the technical problems that the current cement materials have insufficient high temperature mechanical properties and designability, and the cement materials mixed with ceramsite are difficult to construct on site, and provides a method for preparing foam ceramic reinforced cement-based composite materials.

[0005] The method for preparing the foam ceramic reinforced cement-based composite material of the present invention is carried out according to the following steps:

[0006] 1. Mixing cement: Stir three cement raw materials, namely magnesium oxide, phosphate and retarder, in a mixer for 1 to 2 minutes until they are evenly mixed, then add tap water or deionized water, and continue stirring for 1 to 2 minutes until they are evenly mixed again to obtain magnesium phosphate rapid-hardening cement paste; the temperature used in the above cement mixing process is room temperature;

[0007] The mass ratio of magnesium oxide, phosphate and retarder is (4-6):1:(0.28-0.6);

[0008] The mass ratio of the sum of the mass of the magnesium oxide, phosphate and retarder to the mass of tap water or deionized water is 1:(0.1-0.18);

[0009] 2. Pouring cement: quickly pouring the magnesium phosphate rapid-hardening cement slurry prepared in step 2 into the pores of the foam ceramic, and then immediately vibrating, plastering and shaping in sequence to obtain a ceramic-reinforced cement-based composite material preform;

[0010] 3. Curing of the ceramic reinforced cement-based composite material: Curing the ceramic reinforced cement-based composite material preform prepared in step 2.

[0011] In the present invention, foam ceramics of any specifications are used as the skeleton support structure, which provides a support template for the pouring and molding of cement to prevent the collapse of cement during the molding process, and realizes the strengthening effect of ceramics on cement materials. Compared with ceramsite reinforced cement and ceramsite concrete, this new foam ceramic reinforced cement-based composite material has a simple molding process, strong designability and applicability, can be uniformly produced in the factory, and can be quickly assembled on site.

[0012] The foam ceramic reinforced cement-based composite material prepared by the present invention not only has the outstanding high temperature resistance and corrosion resistance of ceramics, but also has the good physical / chemical stability and excellent mechanical properties of rapid-hardening cement materials. At the same time, because the foam ceramic is designed as a skeleton support structure, the designability is effectively improved, and it has broad application prospects in civil engineering.

[0013] The present invention has the following beneficial effects:

[0014] The present invention uses foam ceramics and magnesium phosphate rapid hardening cement to quickly prepare ceramic reinforced cement-based composite materials, solves the problem of insufficient high-temperature mechanical properties of existing cement materials, enables cement-based materials to be strengthened while being rapidly hydrated, expands the application of cement materials in high-temperature fields, avoids the problem of cement materials being difficult to shape by adding admixtures such as ceramsite and rubber, and improves the designability and simplicity of on-site construction of cement-based composite materials. Foam ceramics play a role in strengthening the cement matrix. The foam ceramic structure, on the one hand, realizes the skeleton support of the cement material, and on the other hand, improves the interface bonding between the ceramic reinforcement and the cement matrix. Composite materials of different densities can be obtained by adjusting the ratio of cement and foam ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a photo of the silicon carbide foam ceramic in step 2 of experiment 1;

[0016] Figure 2 This is the overall macroscopic photograph of the foam ceramic reinforced cement-based composite material obtained in experiment five. DETAILED DESCRIPTION

[0017] Specific implementation method 1: This implementation method is a method for preparing a foam ceramic reinforced cement-based composite material, which is specifically carried out according to the following steps:

[0018] 1. Mixing cement: Stir three cement raw materials, namely magnesium oxide, phosphate and retarder, in a mixer for 1 to 2 minutes until they are evenly mixed, then add tap water or deionized water, and continue stirring for 1 to 2 minutes until they are evenly mixed again to obtain magnesium phosphate rapid-hardening cement paste; the temperature used in the above cement mixing process is room temperature;

[0019] The mass ratio of magnesium oxide, phosphate and retarder is (4-6):1:(0.28-0.6);

[0020] The mass ratio of the sum of the mass of the magnesium oxide, phosphate and retarder to the mass of tap water or deionized water is 1:(0.1-0.18);

[0021] 2. Pouring cement: quickly pouring the magnesium phosphate rapid-hardening cement slurry prepared in step 2 into the pores of the foam ceramic, and then immediately vibrating, plastering and shaping in sequence to obtain a ceramic-reinforced cement-based composite material preform;

[0022] 3. Curing of the ceramic reinforced cement-based composite material: Curing the ceramic reinforced cement-based composite material preform prepared in step 2 to complete the entire process of preparing the ceramic reinforced cement-based composite material.

[0023] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the phosphate in step 1 is potassium dihydrogen phosphate. The rest is the same as specific implementation method 1.

[0024] Specific implementation method 3: This implementation method is different from the specific implementation method 1 in that the phosphate in step 1 is diammonium phosphate. The rest is the same as the specific implementation method 1.

[0025] Specific implementation method 4: This implementation method is different from the specific implementation method 1 in that the retarder in step 1 is borax. The rest is the same as the specific implementation method 1.

[0026] Specific implementation method 5: This implementation method is the same as the specific implementation method 1 in that the retarder in step 1 is boric acid. Other aspects are the same as the specific implementation method 1.

[0027] Specific implementation method 6: This implementation method is the same as the specific implementation method 1 in that the retarder in step 1 is sodium tripolyphosphate. Other aspects are the same as the specific implementation method 1.

[0028] Specific implementation example 7: This implementation example is the same as the specific implementation example 1 in that the foam ceramic described in step 2 is silicon carbide foam ceramic. Other aspects are the same as the specific implementation example 1.

[0029] Specific embodiment 8: This embodiment is the same as the specific embodiment 1 in that the foam ceramic described in step 2 is alumina foam ceramic. Other aspects are the same as the specific embodiment 1.

[0030] Specific embodiment 9: This embodiment differs from specific embodiment 1 in that the curing in step 3 is natural curing, specifically placing the ceramic reinforced cement-based composite material preform prepared in step 2 in a natural environment for curing for 7 days. The rest is the same as specific embodiment 1.

[0031] Specific embodiment 10: This embodiment differs from specific embodiment 1 in that the curing described in step 3 is steam curing, specifically, the ceramic reinforced cement-based composite preform prepared in step 2 is kept at room temperature for 4h to 6h, then heated to 40℃ to 60℃ at a heating rate of 5 to 10℃ / h and cured for 7 days. Others are the same as specific embodiment 1.

[0032] The present invention is verified by the following tests:

[0033] Experiment 1: This experiment is a method for preparing a foam ceramic reinforced cement-based composite material, which is specifically carried out according to the following steps:

[0034] 1. Mixing cement: stir three cement raw materials, namely, dead-burned magnesium oxide, potassium dihydrogen phosphate and borax, in a mixer for 1 minute until they are evenly mixed, then add tap water, and continue stirring for 75 seconds until they are evenly mixed again to obtain magnesium phosphate rapid-hardening cement paste; the temperature used in the above cement mixing process is room temperature;

[0035] The mass ratio of the dead-burned magnesium oxide, potassium dihydrogen phosphate and borax is 4:1:0.32;

[0036] The mass ratio of the sum of the mass of the dead-burned magnesium oxide, potassium dihydrogen phosphate and borax to the mass of tap water is 1:0.14;

[0037] 2. Pouring cement: quickly pouring the magnesium phosphate rapid-hardening cement slurry prepared in step 2 into the pores of the silicon carbide foam ceramic until they are filled, and then immediately vibrating, plastering and shaping are performed in sequence to obtain a ceramic-reinforced cement-based composite material preform;

[0038] 3. Natural curing of ceramic reinforced cement-based composite materials: Curing the ceramic reinforced cement-based composite material preform prepared in step 2, placing the preform in a natural environment, without human intervention, curing for 7 days, completing the entire process of preparing the foam ceramic reinforced cement-based composite material.

[0039] The flexural strength was used to evaluate its mechanical properties, and the 7-day room temperature flexural strength was 12.3 MPa.

[0040] Experiment 2: This experiment differs from Experiment 1 in that potassium diammonium phosphate is replaced with diammonium phosphate in step 1. The rest is the same as Experiment 1.

[0041] The flexural strength was used to evaluate its mechanical properties, and the 7-day room temperature flexural strength was 11.8 MPa.

[0042] Experiment 3: This experiment is different from Experiment 1 in that borax is replaced with boric acid in step 1. The rest is the same as Experiment 1.

[0043] The flexural strength was used to evaluate its mechanical properties, and the 7-day room temperature flexural strength was 11.2 MPa.

[0044] Experiment 4: This experiment is different from Experiment 1 in that the mass ratio of dead-burned magnesium oxide, potassium dihydrogen phosphate and borax in step 1 is 5:1:0.36. The rest is the same as Experiment 1.

[0045] The flexural strength was used to evaluate its mechanical properties, and the 7-day room temperature flexural strength was 10.7 MPa.

[0046] Test 5: This test is different from Test 1 in that the mass ratio of the sum of the mass of dead-burned magnesium oxide, potassium dihydrogen phosphate and borax described in step 1 to the mass ratio of tap water is 1:0.16. The rest is the same as Test 1.

[0047] The mechanical properties were evaluated by flexural strength and compressive strength, and the 7-day room temperature flexural strength was 12.9MPa and the compressive strength was 112MPa. The foam ceramic reinforced cement-based composite material sample obtained in Experiment 5 was kept in a muffle furnace at 300℃ for 1h, and its flexural strength was tested to be 8.6MPa and the compressive strength was 104MPa. This shows that the foam reinforced cement-based composite material prepared by this method still maintains 66.7% of the flexural strength and 92.9% of the compressive strength under long-term insulation under high temperature conditions, and has excellent high-temperature mechanical properties.

[0048] Comparative test: This test is different from the first test in that step 2 is eliminated and only steps 1 and 3 are performed. The size of the obtained cement is the same as that of the foam ceramic reinforced cement-based composite material in the first test. Others are the same as the first test. The flexural strength after 7 days of testing is only 8.5MPa, and the compressive strength is only 68MPa.

[0049] Test 6: This test is different from Test 1 in that tap water is added in step 1 and stirring is continued for 90 seconds until the mixture is mixed evenly again. The rest is the same as Test 1.

[0050] The flexural strength was used to evaluate its mechanical properties, and the 7-day room temperature flexural strength was 12.4 MPa.

[0051] Experiment 7: This experiment differs from Experiment 1 in that the silicon carbide foam ceramic is replaced with alumina foam ceramic in step 2. The rest is the same as Experiment 1.

[0052] The flexural strength was used to evaluate its mechanical properties, and the 7-day room temperature flexural strength was 11.2 MPa.

[0053] Test 8: This test is different from Test 1 in that steam curing is performed in step 3: the preform is first kept at room temperature for 5 hours, and then heated to 45°C at a heating rate of 10°C / h for curing for 7 days. Others are the same as Test 1.

[0054] The flexural strength was used to evaluate its mechanical properties, and the 7-day room temperature flexural strength was 13.5 MPa.

[0055] Figure 1 This is a photo of the silicon carbide foam ceramic in step 2 of experiment 1. It can be seen from the picture that the silicon carbide foam ceramic contains many pore structures, and the pore diameters are approximately distributed between 2mm and 3mm. The uneven microstructure of the foam ceramic plays a mechanical bite effect on the cement interface connection, which helps to achieve a better reinforcement effect.

[0056] Figure 2 This is an overall macroscopic photograph of the foam ceramic reinforced cement-based composite material obtained in Experiment 5. The dark gray part is the foam ceramic and the yellow-brown part is the magnesium phosphate cement. It can be seen from the figure that the interface connection quality of the composite material is good, and the cement slurry is poured into the pore structure of the foam ceramic, and the microstructure of the foam ceramic plays a strengthening role.

Claims

1. A method for preparing a foam ceramic reinforced cement-based composite material, characterized in that The method for preparing the foam ceramic reinforced cement-based composite material is carried out according to the following steps:

1. Mixing cement: Stir the three cement raw materials of magnesium oxide, phosphate and retarder with a mixer for 1-2 minutes until they are evenly mixed, then add tap water or deionized water, and continue stirring for 1-2 minutes until they are evenly mixed again to obtain magnesium phosphate rapid-hardening cement paste; the temperature used in the above cement mixing process is room temperature; The mass ratio of magnesium oxide, phosphate and retarder is (4-6):1:(0.28-0.6); The mass ratio of the sum of the mass of the magnesium oxide, phosphate and retarder to the mass of tap water or deionized water is 1:(0.1-0.18); 2. Pouring cement: quickly pouring the magnesium phosphate rapid-hardening cement paste prepared in step 1 into the pores of the foam ceramic, and then immediately vibrating, plastering and shaping in sequence to obtain a ceramic-reinforced cement-based composite material preform; 3. Curing of the ceramic reinforced cement-based composite material: Curing the ceramic reinforced cement-based composite material preform prepared in step 2 to complete the entire process of preparing the ceramic reinforced cement-based composite material.

2. The method for preparing a foam ceramic reinforced cement-based composite material according to claim 1, characterized in that The phosphate described in step 1 is potassium dihydrogen phosphate.

3. The method for preparing a foam ceramic reinforced cement-based composite material according to claim 1, characterized in that The phosphate described in step 1 is ammonium dihydrogen phosphate.

4. The method for preparing a foam ceramic reinforced cement-based composite material according to claim 1, characterized in that The retarder described in step one is borax.

5. The method for preparing a foam ceramic reinforced cement-based composite material according to claim 1, characterized in that The retarder described in step 1 is boric acid.

6. The method for preparing a foam ceramic reinforced cement-based composite material according to claim 1, characterized in that The retarder described in step one is sodium tripolyphosphate.

7. The method for preparing a foam ceramic reinforced cement-based composite material according to claim 1, characterized in that The foam ceramic described in step 2 is silicon carbide foam ceramic.

8. The method for preparing a foam ceramic reinforced cement-based composite material according to claim 1, characterized in that The foam ceramic described in step 2 is alumina foam ceramic.

9. The method for preparing a foam ceramic reinforced cement-based composite material according to claim 1, characterized in that The curing described in step three is natural curing, specifically placing the ceramic reinforced cement-based composite material preform prepared in step two in a natural environment for curing for 7 days.

10. The method for preparing a foam ceramic reinforced cement-based composite material according to claim 1, characterized in that The curing described in step three is steam curing, specifically, keeping the ceramic reinforced cement-based composite preform prepared in step two at room temperature for 4h~6h, then heating it to 40℃~60℃ at a heating rate of 5~10℃ / h and curing it for 7 days.

Citation Information

Patent Citations

  • Method for controlling setting and hardening processes of magnesium phosphate cement

    CN103332960A

  • Production method of foaming ceramic cement building particle light heat preservation composite board

    CN110386782A